STRATEGI INTEGRASI NILAI SPIRITUALITAS DAN PENDIDIKAN KERAKTER DLM KONTES BUDAYA LOKAL UNTUK PEBENTUKAN GENERASI BERAKLHAK MULIAH - Maria Bita Boro (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines strategies for integrating spiritual values and character education based on local wisdom in East Nusa Tenggara (NTT), Indonesia. NTT has a unique socio-cultural characteristic in which Christian and Catholic values have been deeply inculturated into indigenous traditions and customary practices. This qualitative research aims to formulate a model of character education that remains firmly rooted in local cultural foundations (indigenous knowledge) rather than being detached from them. The findings indicate that local concepts such as Moat Gede (Sikka), Suu/Woe (Ngada/Ende), and Loke Nggerang (Manggarai) can function as effective instruments for cultivating noble moral character. The study concludes that the formation of youth character in NTT will achieve optimal outcomes when educational institutions are able to carry out a meaningful “reconciliation” between religious dogma, the formal curriculum, and customary ethical values.